2018
DOI: 10.1002/hbm.24234
|View full text |Cite
|
Sign up to set email alerts
|

Maturational trajectories of local and long‐range functional connectivity in autism during face processing

Abstract: Autism spectrum disorder (ASD) is characterized neurophysiologically by, among other things, functional connectivity abnormalities in the brain. Recent evidence suggests that the nature of these functional connectivity abnormalities might not be uniform throughout maturation. Comparing between adolescents and young adults (ages 14-21) with ASD and age- and IQ-matched typically developing (TD) individuals, we previously documented, using magnetoencephalography (MEG) data, that local functional connectivity in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
52
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 42 publications
(63 citation statements)
references
References 98 publications
9
52
0
Order By: Relevance
“…These ndings are consistent with previous studies reporting that individuals with ASD exhibit reduced PAC during visual gating tasks (46) and face recognition tasks (47,48). Previous studies have proposed that aberrant PAC in ASD is linked to dysregulation of local connectivity and sensory processing.…”
Section: Motor-related Phase-amplitude Couplingsupporting
confidence: 93%
“…These ndings are consistent with previous studies reporting that individuals with ASD exhibit reduced PAC during visual gating tasks (46) and face recognition tasks (47,48). Previous studies have proposed that aberrant PAC in ASD is linked to dysregulation of local connectivity and sensory processing.…”
Section: Motor-related Phase-amplitude Couplingsupporting
confidence: 93%
“…To investigate this further, future studies could use high powered longitudinal ASD samples, to characterise ASSR development throughout childhood and adolescence [64]. If confirmed, divergent ASSR trajectories could act as important autism-relevant markers of intervention efficacy [65].…”
Section: Assrs As Markers Of Dysregulated Local Activitymentioning
confidence: 99%
“…Accordingly, a recent study reported a correlation between the social component of the Autism Diagnostic Observation Schedule (ADOS) and local PAC in an adolescent autistic sample (Mamashli et al, 2018).…”
Section: Pacmentioning
confidence: 99%